031 Delivering safety net advice and the Emergency Department Clinical Quality Indicator of unplanned re-attendance in children. (14th September 2011) - Roland, D; Geliot, T; Patel, A
Abstract : Objectives and Background: A Department of Health study has shown parents of children presenting with fever who did not receive safety net advice were more likely to unnecessarily re-attend. This work aimed to improve the proportion of safety net advice given by junior doctors at the outset of their attachment. In 2009, an audit of feverish children who presented to our Emergency Department found the number of junior doctors providing safety net advice to parents fell from 70.9% in July to 55.9% when a new cohort commenced in August. Methods: A key slide set was introduced into the paediatric induction lecture (given during the Emergency Department's internal programme) regarding safety net advice in August 2010. Results: Following this awareness campaign, an audit involving 457 case notes revealed safety net advice increased significantly from 76.0% in July 2010 to 89.5% in the August cohort. In 2009 there were 41 medically related re-attendances in July (39.0% subsequently admitted) and 48 in August (41.7% admitted). These "return to be admitted" rates were not significantly different (Z value 0.037, p>0.05). In 2010 there were 50 medically related representations in July (40.0% admitted) and 54 in August (27.8% admitted). These "return to be admitted" rates were not significantly different (Z value 1.11, p>0.05). In children aged 16 and over the total number of re-attendees increased from 6.5% to 7.2% between July and August 2010 with the August result significantly higher than the year total (Z value 2.655, p<0.01) although August had the highest re-attendance amount of the year. In children under 16 re-attendees fell from 3.9% to 3.6% between July and August with the August result not being significantly different from the year total (Z value 1.502, p>0.05). Conclusion: The provision of improved safety net advice did not increase the Clinical Quality Indicator of unplanned re-attendance. Induction programmes have an important role to play in promoting evidence-based practice and improving quality.